The growth of the BPJS Ketenagakerjaan brand equity index in 2021 - 2023 - Zainudin, Zainudin; Supriadi, Arief Dahyan; Saragih, Tarimantan Sanberto; Pradana, Fadly Eka; Hutabarat, Rendra HF (International Journal of Innovative Research and Scientific Studies, 2025)
This study aims to analyze the growth of the Brand Equity Index of BPJS Ketenagakerjaan during the 2021–2023 period, focusing on the perception dynamics of active participants, inactive participants, and prospective participants. Through a qualitative approach, this study obtained data through in-depth interviews from a diverse group of participants. The findings indicate that active participants have increasingly positive perceptions of the brand, supported by digital service innovations, effective communication, and satisfying program benefits. Conversely, inactive participants show stagnation or slight declines in perception, influenced by dissatisfaction with previous services and changing personal needs. Prospective participants demonstrate potential brand equity growth, although they still face challenges in understanding the program’s information clearly. This study reveals that the growth trend of BPJS Ketenagakerjaan's Brand Equity Index is influenced by participants' direct experiences, program relevance, and communication strategies. To ensure sustainable growth, BPJS Ketenagakerjaan must enhance service quality, improve communication, and design more personalized loyalty programs for active participants. Additionally, reactivation strategies targeting inactive participants and increased educational campaigns for prospective participants can help strengthen overall brand value. These findings provide valuable insights for BPJS Ketenagakerjaan in designing strategic measures to maintain and enhance brand equity in the future.